Pesan Dakwah dalam Film Series Assalamualaikum yang Tayang di Aplikasi Vidio - Sinta Ayu Kusuma Wardhani; Ahmad Tamrin Sikumbang; Andini Nur Bahri (Maktabatun: Jurnal Perpustakaan dan Informasi, 2021)
This study aims to analyze the message of da'wah in the Assalamualaikum film series that airs on the video application. This study uses a qualitative approach with the method of content analysis which refers to Roland Barthes' semiotic theory by analyzing signs and symbols, so that the message of Islamic da'wah contained denotative, connotative, and mythical meanings. The data collection technique is through scenes from the film series Assalamualaikum. which contain da'wah messages. The results of the research in this film are that there is a da'wah message, namely about aqidah such as saying wallahualam bish-shawab and getting married. The sentence wallahualam bish-shawab means that only Allah SWT knows best while we do not, which teaches us that everything can happen according to the will of Allah SWT. Getting married in this film shows that by getting married, a person has perfected his religion. . Sharia da'wah messages such as covering the genitals, women are required to wear the hijab, and perform prayers. This film series requires women to cover their genitals in accordance with predetermined beliefs, Muslim women are required to wear the hijab, and perform prayers which are one of the main means of prayer, a way to get closer to Allah SWT. Then the message of preaching about morals is to hasten the prayer that we must hasten the prayer when we hear the sound of the call to prayer.